First autochthonous cases of canine thelaziosis in Slovakia: a new affected area in Central Europe - Viktória Čabanová; Peter Kocák; Bronislava Víchová; Martina Miterpáková (Parasites & Vectors, 2017)
Abstract Background The spirurid nematode Thelazia callipaeda, also called the “Oriental eyeworm”, is the causative agent of canine and human ocular thelaziosis. In the past few years it has started to spread across central Europe and new endemic areas have been established. The present study reports on the first four autochthonous cases of canine ocular thelaziosis in the territory of Slovakia, Central Europe. Results All cases were recorded in dogs living in eastern Slovakia, near the border with the Ukraine. All worms collected were investigated morphologically and their identification further confirmed at the molecular level by PCR amplification and direct sequencing. Nucleotide sequences of partial T. callipaeda cox1 and 28S rDNA gene fragments isolated from Slovak dogs were submitted to the GenBank database under accession numbers KY476400 and KY476401, respectively. Conclusions Considering that all four cases were diagnosed in animals that had never travelled abroad, there is clear evidence of an autochthonous occurrence and thereby the further spread of T. callipaeda across Europe. Moreover, at latitude of 48°N, these cases might be considered as the northernmost recorded cases of autochthonous in western and Central Europe.